High thermoelectric performance in p-type InSb with all-scale hierarchical architectures. (October 2022) - Li, Wang; Xu, Tian; Ma, Zheng; Cheng, Yiming; Li, Jinmeng; Jiang, Qinghui; Luo, Yubo; Yang, Junyou
Abstract: We realize the switch of InSb from its intrinsic n-type to p-type semiconductor nature through the substitution of Zn for In. Then, to reduce the high thermal conductivity of p-type InSb, MnO2 is added into p-type InSb matrix. A solid reaction between the MnO2 additives and InSb matrix takes place during spark plasma sintering process. By this approach, the point defect MnIn +, nanoscale In2 O3 precipitates, and microscale MnO2 and Sb secondary phases are formed in InSb. Such all-scale hierarchical architectures play a critical role in the suppression of phonon transport, realizing a low lattice thermal conductivity of 1.50 W/m/K at 733 K for Zn0.04 In0.96 Sb + 3 wt.% MnO2, 58% lower than that of Zn x In1- x Sb. Meanwhile, the Zn0.04 In0.96 Sb + 3 wt.% MnO2 maintains excellent electrical properties (i.e., power factor ∼ 21 μW/cm/K 2 at 733 K). Eventually, the thermoelectric figure of merit ZT of Zn0.04 In0.96 Sb + 3 wt.% MnO2 material reaches 0.54 at 733 K, which is comparable to the well-established peak ZT of n-type InSb at the same temperature, showing promising potential in thermoelectric power generation. Graphical abstract: Image 1 Highlights: All-scale hierarchical architectures were constituted by the solid reaction between MnO2 and InSb. MnO2 corporation doubled the power factor and reduced the thermal conductivity by 58% at 733 K. A high ZT of 0.54 was realized in p-type InSb.